Grace under pressure : leading through change and crisis - Baldoni, John (Ascent Audio, 2023)
"How do leaders ""keep it real"" when times are tough? Grace Under Pressure: Leading Through Change and Crisis focuses on three things leaders need to do when change and adversity strike: take care of their people, take care of themselves, and prepare for the future. And they must do it all with a sense of grace-calmly, collectedly, and compassionately. John Baldoni has established a career as a highly sought-after executive coach, where he's had the privilege of working with senior leaders in virtually every industry from pharmaceutical to real estate, packaged goods to automobiles, and finance to healthcare. He shares his expertise here, focusing on how leaders need to prepare for change by focusing on what matters most-their people. Among the themes Baldoni explores are fear and loss as well as empathy, resilience, and hope. This book also provides a roadmap for leaders seeking to create community as they meet the coming challenges with dignity and grace."